Implementasi Kurikulum 2013 SMA Negeri 8 Surakarta Ditinjau Dari Standar Proses - Fitriana Prihati; Sukarmin Sukarmin (Jurnal Materi dan Pembelajaran Fisika, 2019)
A study was c onducted to investigate the implementation of Curriculum 2013 especially in Physics in SMA Negeri 8 Surakarta. The objective of the research is to describe the implementation of Curriculum 2013 in SMA Negeri 8 Surakarta in terms of process standard including: preparation of RPP, learning activities, and implementation of assessment. The type of research is a survey with the object of research is a teacher of Physics SMA Negeri 8 Surakarta and students of SMA Negeri 8 Surakarta. Descriptive qualitative approach was used in this research. The techniques of data collection include observation, interviews, and documentation. The results showed that the implementation of Curriculum 2013 in SMA Negeri 8 Surakarta viewed from the standard process has not run well. This is shown from: (1) the syllabus and RPP that have not been prepared properly; (2) the learning process that has not used scientific approach; (3) and the assessment that has not been in accordance with Curriculum 2013.